DESIGN OF BIOTECHNOLOGICAL PROCESSES IN THE AGRICULTURAL SECTOR OF UKRAINE - Bashlai, Serhii; Kovalenko, Vladyslav (SWorld-Ger Conference proceedings, 2024)
The article investigates the development of biotechnology in the agricultural business of Ukraine as the main direction of ensuring sustainable development, increasing the competitiveness of the industry and minimizing the negative impact on the environme